Pengaruh Hambatan Samping Terhadap Kecepatan Kendaraan di Daerah Pasar Tradisional - Br Tarigan, Pagit Juni Sartika (Universitas Medan Area, 2024)
Side frictions are often found in traditional market areas on urban roadsides such as Padang Bulan and Tanjung Rejo Setia Budi Traditional Market. It is necessary to know the effect of side frictions on vehicle speed to reduce the impact of traffic jams. Therefore, a survey was conducted on the number of side frictions and speed of the passenger cars and motorbikes. The survey results were processed to determine the correlation coefficient using simple linear regression and determine the direction of the relationship between the influence of side frictions on vehicle speed. Vehicle stopping activity at the Padang Bulan Traditional Market has an interpretation value of 0.551 and 0.241 at the Tanjung Rejo Setia Budi Traditional Market for passenger car speed. Pedestrian activity at the Padang Bulan Traditional Market has an interpretation value of 0.349 and 0.143 for out and in vehicle activity at the Tanjung Rejo Setia Budi Traditional Market for motorbike speed. Based on the direction of the relationship, side frictions to out and in vehicles are the activities that have the highest influence on decreasing vehicle speed. It can concluded that this simple linear regression shows a relationship between side frictions and vehicle speed.